Interconnectedness: the Thread that Enables a Theological and Synodal Response to Abuse - Gill Goulding CJ (Journal of Moral Theology, 2023)
In Greek mythology Ariadne gave a thread to Theseus to enable him to find his way out of the Labyrinth. Interconnectedness is a thread that enables us to see the congruent elements of a theological response to the abuse crisis amidst a spectrum of diverse areas, and move towards a coherent response. I argue that this is a synodal way of proceeding. Key features of this interconnectedness include: an understanding of authority as service and the importance of the child as agent and teacher. Both of these features find their deepest resonance in the person of Christ who issues a clear injunction to pay attention to the child. Indeed, his own identity is inseparable from his being a child in relationship with the Father - the eternal child, always the Son of the Father. There is, I suggest, a challenge to conversion and transformation for the entire ecclesial community.